2019
DOI: 10.1080/23802359.2019.1598788
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast and mitochondrial genomes of Hyunsasi tree, Populus alba x Populus glandulosa (Salicaceae)

Abstract: Populus alba x Populus glandulosa is a hybrid species made by Dr. Hyun. It is called as Hyunsasi tree in Korea. It has been used as a good resource for genetic engineering because it is sterile. Here, we presented its complete chloroplast and mitochondrial genomes: chloroplast genome is identical to that of P. alba (156,505 bp and 129 genes covering 84 protein-coding genes, 37 tRNAs, and eight rRNAs) and mitochondrial genome is 813,261 bp long and GC ratio is 44.9%. It contains 59 genes containing 32 protein-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…This result suggests that next-generation sequencing technology that provides a large number of short reads can be used to provide evidence for the existence of endosymbiont species using DNA extracted from insect species. These results draw comparison to previous studies that have successfully identified a multiple number of complete organelle or bacterial genomes from one NGS library [12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionsupporting
confidence: 65%
“…This result suggests that next-generation sequencing technology that provides a large number of short reads can be used to provide evidence for the existence of endosymbiont species using DNA extracted from insect species. These results draw comparison to previous studies that have successfully identified a multiple number of complete organelle or bacterial genomes from one NGS library [12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionsupporting
confidence: 65%
“…These long gaps on the chloroplast genome are also found in Coffea arabica (Park et al, 2019e), Duchesnea chrysantha (Park et al, 2019c), and Illicium anisatum (Park et al, 2019d). This type of gap was also identified on the mitochondrial genomes of Liriodendron tulipifera (Park et al, 2019b) and Populus alba × glandulosa (Park et al, 2019f).…”
Section: Nucleotide Diversity Among Six Viburnum Speciesmentioning
confidence: 66%
“…It is caused by 6 bp deletion on ycf2 located in the IR region compared to the rest five A. thaliana chloroplast genomes. Interestingly, Tsu0 shows the longest length of chloroplast genome, caused by an insertion of approximately 500 bp between trnL and trnF , which is similar to the cases of Coffea arabica with one continuous insertion region [ 50 ], Duchesnea chrysantha showing three continuous insertion regions [ 21 ], Viburnum amplificatum showing two continuous insertion regions [ 32 ], and mitochondrial genomes of Populus tremula x Populus glandulosa and Liriodendron tulipifera with four and thirty-three continuous insertion regions, respectively [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 87%
“…In addition, A. thaliana and Arabidopsis suecica are clustered because the maternal origin of A. suecica is A. thaliana [ 101 ] ( Figure 7 ). Moreover, the topology of BI tree for the remaining Arabidopsis species, except for A. thaliana and A. suecica , is somewhat inconsistent to those of NJ and ML trees ( Figure 7 ), which has also been found in various plant chloroplast genomes [ 15 , 20 , 28 , 51 , 67 , 69 , 72 , 79 , 91 , 92 , 102 109 ]. This suggests that detailed investigations of phylogenetic relationships among Arabidopsis species with various methods should be done in near future.…”
Section: Resultsmentioning
confidence: 92%